2014
DOI: 10.2215/cjn.10191013
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Outcomes of Kidney Disease in Patients with Pulmonary Hypertension

Abstract: Background and objectives Pulmonary hypertension is associated with higher mortality rates. The associations of nondialysis-dependent CKD and all-cause mortality in patients with pulmonary hypertension were studied.Design, setting, participants, & measurements The study population included those patients who underwent right heart catheterization for confirmation of pulmonary hypertension between 1996 and January 2011. Pulmonary hypertension was defined as the presence of mean pulmonary artery pressure$25 mmHg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 30 publications
1
49
1
2
Order By: Relevance
“…Shah et al [14], in their retrospective analysis of 500 incident PAH patients, demonstrated a univariate association of eGFR with RAP and CI. In 118 incident patients with PH (comprising WHO groups 1, 3, 4, and 5), Leuchte et al [15] also found a significant correlation of creatinine clearance with RAP and CI, while Navaneetha et al [17] observed a significant negative correlation with RAP in 1,088 PH patients (mainly WHO groups 1 and 2) [15]. Conversely, in a recent study in 64 patients with WHO groups 1, 3, and 4 PH, eGFR was significantly correlated with CI only [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shah et al [14], in their retrospective analysis of 500 incident PAH patients, demonstrated a univariate association of eGFR with RAP and CI. In 118 incident patients with PH (comprising WHO groups 1, 3, 4, and 5), Leuchte et al [15] also found a significant correlation of creatinine clearance with RAP and CI, while Navaneetha et al [17] observed a significant negative correlation with RAP in 1,088 PH patients (mainly WHO groups 1 and 2) [15]. Conversely, in a recent study in 64 patients with WHO groups 1, 3, and 4 PH, eGFR was significantly correlated with CI only [18].…”
Section: Discussionmentioning
confidence: 99%
“…Shah et al [14] found an increased risk of death in PAH patients with a serum creatinine above 123 µmol/L, while Kaiser et al [18] identified a nearly 3-fold unadjusted increase in mortality if eGFR was below 80 mL/min/1.73 m 2 . Finally, Navaneethan et al [17] identified a 5% increase in the risk of death per 5 mL/min/1.73 m 2 decrease in eGFR in a heterogeneous cohort of PH (including group 2). Our study demonstrates that CKD at PAH diagnosis is associated with a nearly doubled risk of death, independent of other usual risk factors [4, 5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] PH, defined by elevated pulmonary arterial pressure, is rare in the general population but seen in 30%-40% of patients with ESRD (on the basis of echocardiographic studies). 11,12 After it is established, PH is often progressive and associated with high morbidity and mortality.…”
mentioning
confidence: 99%
“…A recent meta-analysis showed that among all subgroups of patients with HF, the presence of impaired renal function was significantly associated with mortality and had even greater prognostic significance among those with HF with preserved ejection fraction (HFpEF) [3]. Various studies have shown that HF, including HFpEF, is associated with worsening renal function [4-6], with right ventricular (RV) dysfunction and elevated right atrial (RA) pressures being implicated in the pathophysiology of progressive cardiorenal syndrome (CRS) [7, 8]. …”
Section: Introductionmentioning
confidence: 99%